2021
DOI: 10.1111/scs.13045
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare practices and interventions in Europe towards families of older patients with cardiovascular disease: A scoping review

Abstract: Background In Europe, cardiovascular disease is one of the predominant causes of mortality and morbidity among older people over 65 years. The occurrence of cardiovascular disease can have a negative impact on the quality of life of older patients and their families and family health overall. Assuming that illness is a family affair shaped by culture and health care systems, we explored European health care practices and interventions toward families of older patients with cardiovascular disease and heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Additionally, another gap identified is the predominant focus of studies on the functioning of coparenting in structurally diverse families. This can be explained by the lack of a family approach, where the family as a system and a unit of care is not considered in the studies, a gap already described by other reviews (Konradsen et al, 2021;Mahrer-Imhof et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another gap identified is the predominant focus of studies on the functioning of coparenting in structurally diverse families. This can be explained by the lack of a family approach, where the family as a system and a unit of care is not considered in the studies, a gap already described by other reviews (Konradsen et al, 2021;Mahrer-Imhof et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In family nursing care, there might not yet be sufficient evidence to build convincing clinical guidelines on which interventions should be implemented (Mahrer-Imhof et al, 2022). Therefore, high quality intervention studies must be conducted before we can implement services that we know to be helpful for specific populations.…”
Section: Screeningmentioning
confidence: 99%
“…Over the last few decades, nurse researchers have developed knowledge to inform nursing practice with families who share an acute and/or a chronic illness experience with a family member (Beer & Brysiewicz, 2017; Chesla, 2010; Konradsen et al, 2021; Mahrer‐Imhof et al, 2022; Årestedt et al, 2014) However, in many health‐care systems inconsistencies in nursing practices towards families and challenges with the provision of family focused care have been reported (Major et al, 2019; Page et al, 2020; Waid & Kelly, 2020). Family nurse researchers focusing on advancing nursing practice continue to highlight the slow and insufficient integration of family nursing into routine care delivery (Bell, 2014; Duhamel, 2010; Duhamel & Dupuis, 2011; Leahey & Svavarsdottir, 2009; Naef, Massarotto, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lord, 2019;S. Lord et al, 2020;Mahrer-Imhof et al, 2022;Mooney-Doyle et al, 2021). Despite providing evidence of the efficacy of family-focused interventions, the authors of these reviews identified considerable variation in the effects of interventions across families and limited attention to the family variables mediating and moderating intervention efficacy (García-Vivar et al, 2023).…”
mentioning
confidence: 99%